Handling method against service flow - JUNXIAN MO (2007)
The disclosed process method for business flow comprises: besides adding Flow ID cell in PD message, for request message of business flow process, the Anchor SFA converses the SF ID in message into Flow ID and sends the message to PF; the latter authorizes the necessary process for flow ID labeled business flow, and returns the PD Response message; for request message of business flow allocation, it sends message to PF to build business flow, allocate Flow ID, and returns PD Response message containing the Flow ID; the Anchor SFA receives PD Response message to execute relative operation and converse the Flow ID into SF ID, and transmits the PD Response message carrying only the SF ID to other modules for processing till the last one. This invention overcomes defects in prior art.